Indian Entrepreneurial Success in the United States, Canada and the United Kingdom - Robert W. Fairlie; Harry A. Krashinsky; Julie Zissimopoulos; Krishna B. Kumar (Center for Economic Studies and ifo Institute (CESifo), 2013)
Indian immigrants in the United States and other wealthy countries are successful in entrepreneurship. Using Census data from the three largest developed countries receiving Indian immigrants in the world – the United States, United Kingdom and Canada – we examine the performance of Indian entrepreneurs and explanations for their success. We find that business income of Indian entrepreneurs in the United States is substantially higher than the national average and is higher than any other immigrant group. Approximately half of the average difference in income between Indian entrepreneurs and the national average is explained by their high levels of education while industry differences explain an additional 10 percent. In Canada, Indian entrepreneurs have average earnings slightly below the national average but they are more likely to hire employees, as are their counterparts in the United States and United Kingdom. The Indian educational advantage is smaller in Canada and the United Kingdom contributing less to their entrepreneurial success.
Keywords: L26; J15; 330; entrepreneurship; immigration; Indian migrants